Autologous Hematopoietic Stem Cell Transplantation for Treatment of Systemic Sclerosis - Del Papa, Nicoletta; Pignataro, Francesca; Zaccara, Eleonora; Maglione, Wanda; Minniti, Antonina (Frontiers in Immunology, 2018)
Systemic Sclerosis (SSc) is a complex autoimmune disease, characterized by high mortality and morbidity. The heterogeneity in terms of extent, severity, and rate of progression of skin and internal organ involvement gives rise to many difficulties in finding the optimal therapeutic interventions for SSc and, to date, no disease-modifying agents are available. In this scenario, it is not surprising that SSc was one of the first autoimmune diseases challenged with high-dose immunosuppressive treatment followed by autologous hematopoietic stem cell transplantation (AHSCT). In the last decades, AHSCT has emerged as a treatment option for refractory SSc through a reduction of the aberrant immune cells, followed by re-constitution of a new, self-tolerant immune system. After several case series and pilot studies, more recently three randomized controlled trials have shown a benefit in skin involvement, organ functions and quality of life measures in AHSCT compared to monthly cyclophosphamide. In addition, although AHSCT presents a certain risk of mortality, it has been shown that the overall survival is better, compared to the cyclophosphamide group. Current evidence suggests that SSc patients who are most likely to benefit from AHSCT are early, active, with rapidly progressing diffuse skin disease, and in the absence of important involvement of internal organs. As the studies have progressed, it has become evident the need for a more rigorous patient selection, the optimization of transplant and post-transplant procedures, and the intervention of multidisciplinary teams of specialists to increase the safety and efficacy of AHSCT in SSc.